The Importance of Planning to Convert Resources into Outcomes in an Organization - Adhelmi; M.Sirozi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to find out the importance of planning in converting resources (HR) into achievements. Based on the results of this study, it can be concluded that in order to achieve success and competitive advantage, human resource planning (HR) plays an important role in managing human resources effectively and efficiently, namely a good HR planning process by analyzing human resource needs, resource analysis, preparation of HR plans, implementation and monitoring so that the needs of competent human resources will be increasingly met, increasing the effectiveness and efficiency of the Company, can further save the company's costs and budget, encourage more proactive behavior and the creation of harmonious working relationships within the company.